Perbandingan Kadar Bilirubin Direk Pada Pengkonsumsi Alkohol Dan Yang Tidak Mengkonsumsi Alkohol - Agustina Wilhelmimna Djuma; Yofita Weo Kapa (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2017)
Consuming large and continuous amounts of alcohol can cause damage to the body's metabolic system. One of the body's metabolic systems that can be damaged by alcohol is the liver. Alcohol can damage liver cells and can cause various types of liver diseases, such as liver cirrhosis. Liver cirrhosis can be identified from several types of liver function tests, one of which is by examining the levels of direct bilirubin in the serum. The purpose of this study was to examine differences in direct bilirubin levels in alcohol consumption and those who did not consume alcohol. The type of research used was an analytic observation with a case-control study design with 20 subjects who drank alcohol as a case group and 20 subjects who did not consume alcohol as a control group. Measurement of direct bilirubin levels using 24i biolis and unpaired t-test statistics was used to analyze differences in bilirubin levels in both groups. The results of examination of direct bilirubin levels in the case group showed that the average direct bilirubin level was 0.22 mg/dL and the average number in the control group was 0.15 mg/dL, whereas in the unpaired statistical test P value was obtained <0,05. These results showed that there were significant differences in direct bilirubin levels between the case group and the control group.